Brief history of the devlopment of music - Haulenbeck, Marie (My University, 1897)
Introduction: “I have no expectation but that any man will read history aright, who thinks that what was done in a remote age by men whose names have resounded far, has any deeper sense than what he is doing today.” Emerson. No person can truly say that he is a student in music, unless he is well acquainted with its history. Our experience of yesterday teaches us of the today and of the tomorrow. Someone has truly said that history is a great “painter with the world for its canvas and life for a figure.” We of today make the history of those who follow after us. This is especially true of music. We cherish today the magic flute that the Greeks invented. Music in its development has been likened to a child learning to walk, stepping slow hesitatingly at first but gradually faster and with more assurance as each succeeding step. Again, musical history reveals to us the history of mankind. The music of different periods, while it is connected in a logical sense, is not a gradual change from first to last but varies within the different manners and customs of the people of whom and for whom it is written.
Citation: Haulenbeck, Marie. Brief history of the devlopment of music. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Music; History; Theses; Manuscripts (documents)